Improving Sound Transmission Through Triple-Panel Structure Using Porous Material and Sonic Crystal - KIM, Myong Jin (Archives of Acoustics, 2019)
Main aim of this study is to combine the characteristics of the sonic crystal (SC) with acoustic panels and porous materials to improve the sound transmission loss (STL) through the triple-panel structure. SCs cause a bandgap centered around a certain frequency (Bragg’s frequency) due to generation of destructive interference. Initially, an analytical method is developed that extends the previous theory of double-panel structure to predict STL through a triple-panel structure. Finite element (FE) simulations are performed to obtain the STL through the triple-panel, which are validated with the analytical predictions. Various configurations are analyzed using the FE method based on the method of inserting the porous material and SCs between the panels to address the combined effect. STL through the triple-panel structure is compared with that through the double-panel structure having the same total weight and total thickness. It is found that the combined structure of the triple panel and the SC with glass wool as filler gives the best soundproof performance for the same external dimensions. For narrow air gaps, filing with glass wool is more advantageous than inserting one row of SC. In addition, the triple panel combined with a SC has better soundproofing than the two-panel counterparts.